2011
DOI: 10.1016/j.enbuild.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic procedure to study the influence of occupant behavior on building energy consumption

Abstract: Efforts have been devoted to the identification of the impacts of occupant behavior on building energy consumption. Various factors influence building energy consumption at the same time, leading to the lack of precision when identifying the individual effects of occupant behavior. This paper reports the development of a new methodology for examining the influences of occupant behavior on building energy consumption; the method is based on a basic data mining technique (cluster analysis). To deal with data inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
167
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(191 citation statements)
references
References 10 publications
1
167
0
3
Order By: Relevance
“…Occupant behaviour in buildings, e.g. heating behaviour, window opening behaviour, has been suggested to be one of the main aspects causing this gap (de Wilde 2014), due to its great impact on the building performance, which has been demonstrated in a number of existing studies using data from either real buildings (Mulville, Jones, and Huebner 2013;Yu et al 2011;Gram-Hassen 2010;Gill et al 2010;Brown, Dowlatabadi, et al 2009;Bağcı 2009;Guerra Santin, Itard, and Visscher 2009;Steemers and Yun 2009;Hass, Auer, and Biermayr 1998) or building simulation (Bonte, Thellier, and Lartigue 2014;Lee and Malkawi 2014;Mavrogianni et al 2014;Roetzel 2014;Silva and Ghisi 2014;de Meester et al 2013;Fabi, Andersen, and Corgnati 2013). These studies, however, focused on the building design stage and operation stage, while the impact of occupant behaviour in the building refurbishment stage still requires further exploration, especially its impact on the predicted energy saving potential of refurbishment measures by dynamic building performance simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Occupant behaviour in buildings, e.g. heating behaviour, window opening behaviour, has been suggested to be one of the main aspects causing this gap (de Wilde 2014), due to its great impact on the building performance, which has been demonstrated in a number of existing studies using data from either real buildings (Mulville, Jones, and Huebner 2013;Yu et al 2011;Gram-Hassen 2010;Gill et al 2010;Brown, Dowlatabadi, et al 2009;Bağcı 2009;Guerra Santin, Itard, and Visscher 2009;Steemers and Yun 2009;Hass, Auer, and Biermayr 1998) or building simulation (Bonte, Thellier, and Lartigue 2014;Lee and Malkawi 2014;Mavrogianni et al 2014;Roetzel 2014;Silva and Ghisi 2014;de Meester et al 2013;Fabi, Andersen, and Corgnati 2013). These studies, however, focused on the building design stage and operation stage, while the impact of occupant behaviour in the building refurbishment stage still requires further exploration, especially its impact on the predicted energy saving potential of refurbishment measures by dynamic building performance simulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several decades, it has been successfully applied in economics, retails, telecommunication, and financial services [4]. Recently, efforts have also been made to investigate the application of data mining in HVAC field, including building energy consumption prediction [5,6], building energy management [7,8], fault detection and diagnosis [9,10], and occupant behaviour [11,12].…”
Section: Technical Approachmentioning
confidence: 99%
“…The need for end-users to be guided through the workings of the unconventional systems cannot be overemphasised. Literature sources have indicated that occupants behaviour or 'people factors' as described by James E. Piper, bear greatly on the building performance (Yu et al, 2011;Masoso and Grobler, 2010;Piper, 1999). Yu et al (2011) reported a study by Ouyang and Hakao (2009) which investigated energy-saving potential by improving user behaviour using 124 households in China.…”
Section: Introductionmentioning
confidence: 99%
“…Literature sources have indicated that occupants behaviour or 'people factors' as described by James E. Piper, bear greatly on the building performance (Yu et al, 2011;Masoso and Grobler, 2010;Piper, 1999). Yu et al (2011) reported a study by Ouyang and Hakao (2009) which investigated energy-saving potential by improving user behaviour using 124 households in China. The 124 houses were divided into two groups; one group was educated to promote energy-conscious behaviour and adopt corresponding energy saving measures, while the second group not educated, they were expected to keep the status-quo.…”
Section: Introductionmentioning
confidence: 99%